Notting Hill [videorecording (DVD)] - Michell, Roger, 1956-; Roberts, Julia, 1967-; Grant, Hugh; Bonneville, Hugh; Chambers, Emma, 1964-; Dreyfus, James; Ifans, Rhys, 1967-; McInnerny, Tim; McKee, Gina, 1964- (Universal Studios, 1999)
The world's most famous movie star falls in love with a small-time bookstore owner.